Integrating multibeam echosounder water‐column data into benthic habitat mapping. Issue 8 (7th June 2022) - Porskamp, Peter; Schimel, Alexandre C. G.; Young, Mary; Rattray, Alex; Ladroit, Yoann; Ierodiaconou, Daniel
Abstract: Kelp forests worldwide are under increasing pressure from anthropogenic impacts including kelp harvesting, pollution, and higher sea surface temperatures due to climate change. Accurate mapping of these habitat types is required to inform effective conservation policies. We show that adding the acoustic energy from the multibeam echosounder water‐column data immediately above the seafloor as a variable in models of the distribution of benthic marine habitats can significantly improve the accuracy of the resulting maps, specifically for habitat categories that include large species of macroalgae on shallow subtidal reefs. Observations from a comprehensive towed‐video survey were used as ground‐truth and classified according to a hierarchical marine biotope classification scheme. The multibeam echosounder water‐column data were processed into a 2D layer akin to a seafloor backscatter mosaic, but instead representing the average acoustic energy in a layer 0–1 m above the seabed, excluding the echo from the seafloor itself and after filtering the specular artifact. Including this "water‐column mosaic" in models increased the maps' overall accuracy by up to 1.18 percent points and improved producer accuracies for habitats that contained macroalgae by up to 2.95 percent points. With increasing pressure on temperate macroalgal communities arising from warming oceans, our work provides a timely advance for mapping these critical habitats and monitoring changes in their distribution.